Advanced mycotoxin control and decontamination techniques in view of an increased aflatoxin risk in Europe due to climate change - Loi, Martina; Logrieco, Antonio F.; Pusztahelyi, Tünde; Leiter, Éva; Hornok, László; Pócsi, István (Frontiers in Microbiology, 2023)
Aflatoxins are toxic secondary metabolites produced by Aspergillus spp. found in staple food and feed commodities worldwide. Aflatoxins are carcinogenic, teratogenic, and mutagenic, and pose a serious threat to the health of both humans and animals. The global economy and trade are significantly affected as well. The incidence of aflatoxin is much more unpredictable in the climate change and growing population scenarios, given that mould growth and aflatoxin production are deeply affected by environmental factors, like water activity, temperature, drought stress, soil pH and electrical conductivity. The risk of a shift in traditional occurrence areas for aflatoxins is expected globally and in southeast Europe due to the increasing average temperatures. Various models and datasets related to aflatoxins in maize have been developed and used but have not yet been linked. The prevention of crop loss due to aflatoxin contamination is complex and challenging. Hence, the set-up of advanced decontamination is crucial to cope with the challenge of climate change, growing population, unstable political scenarios, and food security problems also in European countries. After harvest, decontamination methods can be applied during transport, storage, or processing, but their application for aflatoxin reduction is still limited. Therefore, this review aims to investigate the effects of environmental factors on aflatoxin production because of climate change and to critically discuss the present-day and novel decontamination techniques to unravel gaps and limitations to propose them as a tool to tackle an increased aflatoxin risk in Europe.